Intra-arterial chemotherapy for retinoblastoma: 8-year experience from a tertiary referral institute in Thailand - Duangnate Rojanaporn (2020)
Copyright © 2019 by Asia-Pacific Academy of Ophthalmology. Purpose: To study the safety and efficacy of intra-arterial chemotherapy (IAC) as a treatment for intraocular retinoblastoma in Thailand. Design: Retrospective, interventional case series. Methods: In this study, IAC was performed as primary or secondary treatment for patients with intraocular retinoblastoma using melphalan with or without additional topotecan or carboplatin. Survival rate, globe salvage rate, and treatment complications were recorded and analyzed. Results: Of 27 eyes of 26 patients with retinoblastoma, 7 (26%) had IAC as primary treatment and 20 (74%) had IAC as secondary treatment. The eyes were classified by International Classification of Retinoblastoma (ICRB) as group B (n = 3, 11%), group C (n = 1, 4%), group D (n = 12, 44%), and group E (n = 11, 41%). Catheterization was successful in 75 (94%) of 80 sessions. The median number of IAC sessions was 3 (range, 1–7). At a mean follow-up of 32 months (range, 3–95 months), the overall globe salvage rate was 52%, with 100% in groups B and C, 75% in group D, and 9% in group E. Complications of IAC included occlusive vasculopathy (n = 4, 15%), vitreous hemorrhage (n = 3, 11%), retinal artery precipitation (n = 2, 7%), strabismus (n = 2, 7%), and transient ischemic attack (n = 1, 4%). The overall survival rate was 96% (n = 25). Conclusion: Our experience suggests that IAC is a safe and effective treatment for patients with ICRB group B, C, D, and some group E retinoblastoma. Careful patient selection and experienced surgeons are critical for achieving the best treatment outcome.